PROSPEK USAHA INOVASI PRODUK KAPSUL BAWANG HITAM SEBAGAI SUMBER ANTIOKSIDAN PENANGKAL RADIKAL DALAM MENGHADAPI PANDEMI - Utami, Ratih Apri; Anarofida, Anarofida; Pratiwi, Meihilda Dona; Purborini, Ajeng Gendis; Putri, Dhea Karunia; Annisa, Rofiu Sisil (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2023)
In the era of the Covid-19 pandemic, an immune booster is really needed which can make a person's immune system more immune to the corona virus. Therefore, the product "SULANTAM ABS" is present as a body endurance supplement. "SULANTAM ABS" (Safe, Efficacious, Healthy Black Onion Capsules) is an innovation from black onions which is made in capsule form and aims to make it easier for consumers to consume it so that it is more effective, efficient and hygienic. The objectives of this program include: 1) Fulfilling consumer needs as an immune system supplement, 2) Increasing public knowledge about the benefits of black garlic, and 3) Creating innovation from black garlic supplement products in capsule form. The method for making the product "SULANTAM ABS" includes the stages of fermentation, drying, flouring and packaging. Sales of this product were carried out from August to September 2021, 20 units of the product were sold with a turnover of IDR 1,100,000, profit IDR 201,000. and BEP Rp. 96,766. This sales method is mainly carried out online through e-commerce and offline through consignment. Based on these results, this business is very profitable and beneficial to society.